Rediscovery of two Orange Flat skipper butterflies, Pintara tabrica (Hewitson, [1873] and Pintara pinwilli (Butler, [1879]), (Lepidoptera: Hesperiidae: Pyrginae) from Northeast India - Gogoi, Monsoon Jyoti; Dwari, Saurav (Journal of the Bombay Natural History Society (JBNHS), 2023)
No Absatract.